Correlation properties of the accompanied particle motion relate motion main particles in processes of radioactive decay and internal conversion - M. F. Mitrokhovich (Ядерна фізика та енергетика)
On installation of coincidences of -quanta with electrons and with law energy electrons close to zero area the spatial correlation of the direction emitting accompanying eas particles (electron "shake-off", Auger electron) with respect to the primary particle em (electron) at -decay or internal conversion of transitions in 152Eu decay have been investigated. By measuring the double- eac and triple eacem-coincidences the correlating  = 4dP/Pd movement of the accompanying particle and the main particle in the same hemisphere emission ( = 0) and in opposite hemispheres emission ( = 2) were measured. It was received that  ( = 0) >> 1, and  ( = 2) << 1. It is discussed the mechanism of strong spatial correlation in the motion of accompanying particle with the main particle in the process of radioactive decay and internal conversion for the account of current compo-nents of electron-electron interaction in the final state particles.